STUDI LITERATUR SISTEMATIS: IMPLEMENTASI TATA KELOLA TEKNOLOGI INFORMASI BERBASIS COBIT DI SEKTOR PENDIDIKAN - Rahma Khalida; Winda Yulitasari; Muhammad Qomarul Huda (P3M Politeknik Negeri Banjarmasin, 2026)
The digital transformation era drives educational institutions to manage information technology (IT) systematically to align with organizational strategy and support academic performance. However, challenges such as strategy–IT misalignment, limited resources, and inconsistent governance practices are still common. This study aims to analyze the implementation of COBIT-based IT governance in the education sector, identify its benefits, challenges, comparative effectiveness with other frameworks, and key success and failure factors. A Systematic Literature Review (SLR) approach was employed by searching articles in Scopus and Google Scholar databases, applying inclusion–exclusion criteria, and performing thematic analysis on 26 selected studies. The findings reveal that COBIT improves strategy–IT alignment, process standardization, decision transparency, and accreditation compliance, while providing an objective mechanism for IT project portfolio prioritization. Key challenges include limited analytical capacity, inconsistent documentation practices, and resource constraints. These results highlight COBIT’s role as a continuous improvement tool and provide practical implications for educational institutions to strengthen human resources, standard operating procedures, and continuous evaluation mechanisms.